Analisis Covid-19 terhadap Usaha Mikro Kecil dan Menengah (UMKM) di Kabupaten Tulang Bawang Tahun 2020 - Dedy Yuliawan; Veronica Wanniatie (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2021)
Corona Virus Disease 2019 (Covid-19) entering Indonesia has an impact on restricted population mobility. In addition, Pembatasan Sosial Berskala Besar Policy (PSBB) affects the national economy, especially Micro, Small, and Medium Enterprises (MSMEs). It has a spillover effect in the lowest areas, including the Tulang Bawang Regency. This study uses a survey method with closed and open questions with respondents as many as 100 MSMEs in Tulang Bawang Regency to determine the impact of Covid-19 and how MSME strategies can overcome it. The results show that overall, MSMEs experience an adverse effect, but there are several types of MSMEs that continue to experience an increase. In addition, some MSMEs can adjust their business strategies through marketing changes through online sales, but MSME actors with low levels of education have difficulty.